THE INFLUENCE OF ELECTRONIC WORD OF MOUTH, BRAND IMAGE, BRAND AWARENESS ON PURCHASE INTENTION OF PALETAS WEY ICE CREAM - Reky Ifan Ariyo; Kristina Anindita Hayuningtias (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Social media is a key platform for consumers to share product experiences and obtain information in today's digital era. This study examines how brand awareness, brand image, and electronic word-of-mouth (E-WOM) influence consumers' intention to purchase Paletas Wey ice cream. Purposive sampling and a quantitative approach were used to find respondents who knew Paletas Wey through offline retailers or social media. An online survey was used to collect data, and Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method was applied for analysis. The findings show that brand image and brand awareness have a positive and significant effect on purchase intention, and that E-WOM has a positive and significant effect on both variables. The majority of variation in consumer purchase intentions can be explained by this model. This research suggests that brand familiarity, brand image, and online reviews play an important role in shaping consumer purchase intentions. Keywords: Electronic Word-of-Mouth; Brand Image; Brand Awareness; Purchase Intention; Social Media